A Comprehensive Study on Nutritive Value, Polyphenol Constituents and Prevention of Pathogenic Microorganism by Different Resin Extracts of Commiphora myrrh - Rasha Khalid Abbas; Amina A.M. Al-Mushhin; Fatima S. Elsharbasy; Kother Osman Ashiry (Microbiology and Biotechnology Research: An Overview Vol. 2, 2025)
Commiphora myrrh are small tree family Burseraceae. The resin extract of Commiphora myrrh is Widely used in folk medicine. The study of myrrh resin extract includes moisture. Minerals such as (Ca, Fe, Mg, Na, Cu and Zn), protein, total fat and crude fiber. This study used a Muffle furnace, Kjeldahl methods Soxlet and atomic absorption. HPLC is used to evaluate Polyphenol constituents of myrrh in different resin extracts (ethanol, ethyl acetate, petroleum ether and chloroform) as Conc. (µg / g) and in all extracts (ethanol, ethyl acetate and petroleum ether and chloroform) it contained Chlorogenic acid, gallic acid Catechin, Coffeic acid, caffeine, Syringic acid, Coumaric acid, Ferulic acid, Naringenin, 4`.7-Dihydroxyisoflavone, Cinnamic, Propyl Gallate Vanillin, Querectin and Acid Ellagic acid in different concentration percentage and area The effect of Commiphora myrrh (ethanol, ethyl acetate, petroleum ether and chloroform) resin extract against four different pathogenic bacteria Salmonella typhimurium, Pseudomona aeruginosa, Escherichia coli, and Bacillus cereus, were examined by Mueller Hinton Agar and measuring inhibition zone (diameter mm), show that there were significantly different among bacteria and different method of extract. All different Commiphora myrrh seed extracts (aqueous, ethyl acetate and petroleum ether) have high activity against Candida albicans fungus. The study was conducted to identify the Commiphora myrrh nutritive value, polyphenol Compound and the activity against bacteria and fungi. In conclusion, Commiphora myrrh contains polyphenol compounds that have potent antioxidant, antibacterial and antifungal activity in all different leaf extracts.